Complex forelimb movements and cortical topography evoked by intracortical microstimulation in male and female mice. (3rd May 2022) - Brown, Andrew R; Mitra, Shaarang; Teskey, G Campbell; Boychuk, Jeffery A
Abstract: The motor cortex is crucial for the voluntary control of skilled movement in mammals and is topographically organized into representations of the body (motor maps). Intracortical microstimulation of the motor cortex with long-duration pulse trains (LD-ICMS; 500 ms) evokes complex movements, occurring in multiple joints or axial muscles, with characteristic movement postures and cortical topography across a variety of mammalian species. Although the laboratory mouse is extensively used in basic and pre-clinical research, high-resolution motor maps elicited with electrical LD-ICMS in both sexes of the adult mouse has yet to be reported. To address this knowledge gap, we performed LD-ICMS of the forelimb motor cortex in both male ( n = 10) and naturally cycling female ( n = 8) C57/BL6J mice under light ketamine-xylazine anesthesia. Complex and simple movements were evoked from historically defined caudal (CFA) and rostral (RFA) forelimb areas. Four complex forelimb movements were identified consisting of Elevate, Advance, Dig, and Retract postures with characteristic movement sequences and endpoints. Furthermore, evoked complex forelimb movements and cortical topography in mice were organized within the CFA in a unique manner relative to a qualitative comparison with the rat.